Moon Great Smoky Mountains National Park : hiking camping scenic drives - Frye, Jason (Berkeley, CA: Avalon Travel, Hachette Book Group, 2022)
From majestic mountaintops to lush forests and untouched wilderness, take in the best of the Smokies with Moon Great Smoky Mountains National Park. Moon Great Smoky Mountains National Park features: Itineraries for every timeline and budget, ranging from one day in the park to a week-long trip, including: Best of the Smokies, Family Fun, Escape the Crowds, and Best Hikes; Strategies for getting around the Great Smoky Mountains, avoiding crowds, and exploring the less-visited areas of the park; In-depth coverage of gateway cities and towns in both Tennessee and North Carolina, including Gatlinburg, Asheville, Pigeon Forge, and Knoxville, as well as worthwhile stops like Cherokee, Bryson City, and Maggie Valley; Full-color, vibrant photos and detailed maps throughout; Expert tips for travelers looking to go hiking, biking, zip-lining, rafting, and more, plus essential packing and health and safety information; The top activities and unique ideas for exploring the park: Cruise along Newfound Gap Road for epic views and scenic overlooks, try your hand at fly-fishing, and enjoy the refreshing solitude of a night camping under the stars. Hike to beautiful waterfalls, catch a glimpse of the buzzing fireflies, and sample a little local moonshine. Visit remnants of the region's historic settlements, spot local wildlife, or explore the bustling nearby cities; Valuable insight from nature lover and Smoky Mountains aficionado Jason Frye; Honest advice on where to stay inside and outside the park, including the best spots to pitch a tent, park your RV, or relax at an upscale resort; Up-to-date information on park fees, passes, and reservations; Recommendations for families, LGBTQ+ travelers, seniors, international visitors, travelers with disabilities, and traveling with pets; Thorough background on the wildlife, terrain, culture, and history.
Includes bibliographical references and index
Keywords: National parks and reserves -- Guidebooks -- North Carolina; National parks and reserves| -- Guidebooks -- Tennessee; Great Smoky Mountains National Park (N.C. and Tenn.)